Petrological and geochemical study of Birimian ultramafic rocks within the West African Craton: Insights from Mako (Senegal) and Loraboué (Burkina Faso) lherzolite/harzburgite/wehrlite associations. (February 2020) - Labou, Ibrahima; Benoit, Mathieu; Baratoux, Lenka; Grégoire, Michel; Ndiaye, Papa Moussa; Thebaud, Nicolas; Béziat, Didier; Debat, Pierre
Abstract: In Archean and Paleoproterozoic greenstone belts, ultramafic (UM) rock occurrences are commonly found in close association within basic and differentiated magmatic series. In the Kedougou-Kenieba Inlier (West African Craton), UM rocks are interbedded within the Birimian (2.1 Ga) Mako tholeiitic series (basalts, gabbros). UMs are typically lherzolite, harzburgite and wehrlite, characterized by their cumulative textures and relative proportions of chromite, olivine, clinopyroxene, amphibole ± orthopyroxene. Geochemical study (Major, REE and trace elements in whole rocks and mineral (mainly clinopyroxene and amphibole) and Sr/Nd isotopic records suggest the existence of different types of complexes. The first one consists of lherzolite + harzburgite assemblages whereas the second one consists of isolated wehrlite massifs. Both complexes highlight two different geodynamic environments, the first association being significantly more juvenile or mantle-related than isolated wehrlites which show more evolved geochemical signatures. UM rocks (dunite + wehrlite) of Loraboué (greenstone belt of Boromo, Burkina Faso) associated with calc-alkaline series display the same mineralogical composition as the Mako UM rocks but exhibit a different whole rock composition characteristic of mature island-arc magmas and showing U-shaped REE pattern for both clinopyroxene and host rock, and a clear negative Nb anomaly. The Mako UMs suggest that this portion of the Birimian crust was built in an oceanic context evolving from a MORB-like domain to an increasingly mature volcanic arc domain. Highlights: Trace elements and Nd isotopes show two types of ultramafic complexes at Mako area. The two UM complexes are set up in two different geodynamic contexts (MORB and arc). Wehrlites of Mako and Loraboué areas have very different geochemical characteristics. The Loraboué area represents more mature arc environment compared to the Mako area. The Birimian crust was built in a MORB context progressively becoming a mature arc.